THE VARIABLE SKY OF DEEP SYNOPTIC SURVEYS - Ridgway, Stephen T.; Matheson, Thomas; Mighell, Kenneth J.; Olsen, Knut A.; Howell, Steve B. (The Astrophysical journal, 2014)
The discovery of variable and transient sources is an essential product of synoptic surveys. The alert stream will require filtering for personalized criteria-a process managed by a functionality commonly described as a Broker. In order to understand quantitatively the magnitude of the alert generation and Broker tasks, we have undertaken an analysis of the most numerous types of variable targets in the sky-Galactic stars, quasi-stellar objects (QSOs), active galactic nuclei (AGNs), and asteroids. It is found that the Large Synoptic Survey Telescope (LSST) will be capable of discovering ~10 super(5) high latitude (|b| > 20[degrees]) variable stars per night at the beginning of the survey. (The corresponding number for |b| < 20[degrees] is orders of magnitude larger, but subject to caveats concerning extinction and crowding.) However, the number of new discoveries may well drop below 100 per night within less than one year. The same analysis applied to GAIA clarifies the complementarity of the GAIA and LSST surveys. Discovery of AGNs and QSOs are each predicted to begin at ~3000 per night and decrease by 50 times over four years. Supernovae are expected at ~1100 per night, and after several survey years will dominate the new variable discovery rate. LSST asteroid discoveries will start at >10 super(5) per night, and if orbital determination has a 50% success rate per epoch, they will drop below 1000 per night within two years.